2008
DOI: 10.1016/s0377-1237(08)80013-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Hepatitis B Surface Antigen in Vaccinated Health Care Workers

Abstract: Background: Health care workers (HCWs) in Armed Forces are immunised against Hepatitis B virus (HBV), however they are not subjected to anti-HBs (antibody to Hepatitis B surface antigen) assessment after primary vaccination. The present study was undertaken to determine the protection offered by HBV vaccine in HCW. Methods: Cross-sectional study was carried out at tertiary care hospital. A total 146 HBV vaccine compliant HCW were evaluated for quantitative anti-HBs by enzyme immune assay. Result: 129 (88.4%) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…13 It is considered that those individuals with an anti-HBs concentration of ≥10 mIU/mL were immune against HBV infection, while those with an anti-HBs concentration of <10 mIU/mL might re-quire an additional booster vaccine dose. [14][15][16] The specific antibodies against different HBV protein components are one of the major approaches for B cells to be involved in anti-HBV infection, such as antibody to hepatitis B core antigen (anti-HBc), antibody to hepatitis B e antigen (anti-HBe) and anti-HBs. Anti-HBc and anti-HBe serve as diagnostic biomarkers for HBV infection, while anti-HBs antibody is the only antibody that can specifically recognize and bind to HBsAg, 17,18 thus serving an important role in HBsAg clearance.…”
Section: Protective Role Of Antibody In Hbv Control and Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…13 It is considered that those individuals with an anti-HBs concentration of ≥10 mIU/mL were immune against HBV infection, while those with an anti-HBs concentration of <10 mIU/mL might re-quire an additional booster vaccine dose. [14][15][16] The specific antibodies against different HBV protein components are one of the major approaches for B cells to be involved in anti-HBV infection, such as antibody to hepatitis B core antigen (anti-HBc), antibody to hepatitis B e antigen (anti-HBe) and anti-HBs. Anti-HBc and anti-HBe serve as diagnostic biomarkers for HBV infection, while anti-HBs antibody is the only antibody that can specifically recognize and bind to HBsAg, 17,18 thus serving an important role in HBsAg clearance.…”
Section: Protective Role Of Antibody In Hbv Control and Clearancementioning
confidence: 99%
“… 13 It is considered that those individuals with an anti-HBs concentration of ≥10 mIU/mL were immune against HBV infection, while those with an anti-HBs concentration of <10 mIU/mL might require an additional booster vaccine dose. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…Although the percentage of female protective responders was greater (85.5%) compared to male protective responders (75.9%), the association of anti-HBs status and gender was not statistically significant. Ashmaki et al, Chaudhari et al observed that anti-HBs titer due to gender factor was not statistically significant [22,23]. Also research studies have reported increased percentage of non-protective responders among males as compared to females [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…in their study among HCP in armed forces showed a 93.8% response in participants <30 years compared to only 77.5% response in those who were >30 years of age. [ 19 ] Gara et al . (2014) tested anti-HBs levels at a clinical center in Bethesda and concluded that anti-HBs levels decrease after 10–31 years and fall below a level considered protective in approximately 25% of HCWs.…”
Section: Discussionmentioning
confidence: 99%